Tindak Pidana Promosi Judi Online Melalui Media Sosial - Utami, Putu Ananda Nadya; Antari, Putu Eva Ditayani (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The promotion of online gambling via social media has had a negative impact due to technological advances. This prohibition is regulated by the ITE Law, and the criminal threats listed here are sufficient to prevent perpetrators from taking action. The formulation of the Panaliten's pitakonan iki includes types of criminal acts that are prosecuted by perpetrators of online gambling advertisements via social media and factors that contribute to the prosecution of perpetrators. The method of panaliten ingkang dipunginakaken high menika empiri kanthi analytical descriptive approach ingkang includes legal and factual perspectives. The findings of the Nedahaken Panaliten bilih type of offense of ingkang are punishable by perpetrators of online gambling promotion who are subject to adhedhasar, the threat of imprisonment and criminal punishment of ingkang and haraken wonten ing Article 45 paragraph (1) read in conjunction with Article 27 paragraph (2). This indicates that a prison sentence will be imposed enforcement by the Bali Police Special Crime Director involve resource constraints. humans, difficulties in collecting evidence and arresting perpetrators, server factors located in countries where gambling is legal, lack of public awareness and concern, and rapid technological advances